Optimalisasi Perawatan Terhadap Guna Meminimalisir Gangguan Terhadap Lokomotif CC 203 Di Daop 2 Bandung - Usworo, Restu Fajar Widi; AS, Hartono; Pratama, Uriansah (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2019)
Daop 2 Bandung has the potential for high passenger rail transport. With the high demand for passenger transport both for local rail transport and long-distance rail transport, the driving force condition in this case is the locomotive is very influential. Judging from the need for rail transport services, the increasing reliability of the driving facilities, especially the locomotive is very supportive in the operation of rail transport. The mean travel has exceeded the tolerant level of locomotive disturbance that is as much as 30 times the disturbance / 1 million km traveled and the dominant interference occurs in the locomotive CC 203 is the weak power disturbance, hot engine, heat. It is recommended to carry out maintenance of locomotive CC 203 based on the predominant disturbance in locomotive, optimize maintenance of locomotive CC 203 in accordance with applicable SOP, preventive measures and should be cultivated to re-check treatment